2022
DOI: 10.3390/su14020889
|View full text |Cite
|
Sign up to set email alerts
|

Does Culture Matter? Measuring Cross-Country Perceptions of CSR Communication Campaigns about COVID-19

Abstract: The COVID-19 pandemic has brought several challenges to businesses and societies. In response, many corporations have supported local communities and authorities in the management of the pandemic. Although these initiatives, which can be considered forms of corporate social responsibility (CSR), were highly coupled with explicit CSR communication campaigns, little is known about whether these campaigns were effective. Previous research indicates that culture can shape people’s perceptions of CSR initiatives an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This last aspect refers to the constant cooperation that would be required between the bodies working in the field of health and governments which, as it was found during this health crisis, have the responsibility to inform the public, on a large scale, about the policies that need to be applied in the context of the occurrence and application of COVID-19 vaccines. With regard to the way in which informal institutions shape the receptivity to the messages of the authorities in the fight against COVID-19, it was noted that culture plays a crucial role (Airhihenbuwa et al, 2020 ; Colleoni et al, 2022 ). Belonging to certain values influences the behavior of individuals, including the degree of acceptance of government measures for combating COVID-19 and, for this reason, the ex-communist regime can be cited as a cause of disparities created between Eastern and Western Europe.…”
Section: Resultsmentioning
confidence: 99%
“…This last aspect refers to the constant cooperation that would be required between the bodies working in the field of health and governments which, as it was found during this health crisis, have the responsibility to inform the public, on a large scale, about the policies that need to be applied in the context of the occurrence and application of COVID-19 vaccines. With regard to the way in which informal institutions shape the receptivity to the messages of the authorities in the fight against COVID-19, it was noted that culture plays a crucial role (Airhihenbuwa et al, 2020 ; Colleoni et al, 2022 ). Belonging to certain values influences the behavior of individuals, including the degree of acceptance of government measures for combating COVID-19 and, for this reason, the ex-communist regime can be cited as a cause of disparities created between Eastern and Western Europe.…”
Section: Resultsmentioning
confidence: 99%
“…The subset used for this study was a portion of the large dataset collected as an effort to grasp the public’s cognitive, affective, and behavioral responses toward COVID-19 in different continents over the world, other parts of which were present in other publications ( Choi et al, 2022 ; Colleoni et al, 2022 ). We conducted an online survey of U.S. adults from October through November 2020.…”
Section: Methodsmentioning
confidence: 99%
“…It has been observed that the majority of studies conducted during COVID-19 focused on the perspectives of employees and customers in relation to reporting and CSR communication [40]. Specifically, financial reports were used to examine their correlation with fraud in financial statements, changes in profitability, and other factors [36].…”
Section: Prior Research On Covid-19 and Ceo Messagesmentioning
confidence: 99%